PENGARUH SOCIAL eWOM PADA INSTAGRAM TERHADAP BRAND ATTITUDE DAN PURCHASE INTENTION SMARTPHONE OPPO DI SURABAYA - Patrick Surya Putra (Perpustakaan Universitas Surabaya, 2020)
The Purpose of this study was to identify and analyze the influnce of social eWOM in instagram on brand attitudes and purchase intentions with Oppo smartphone object in Surabaya. The type of research is basic research. In this study 3 variable are use (social eWOM, brand attitudes and purchase intentions). Source of data used is primary data that is by distributing questionnaires. The samples used in this study was 110 respondents that distibuted in Surabaya. The sampling technique used was convenience sampling and the data will be processed using SPSS 18.0 for windows and AMOS 22.0. The results of this study indicate that social eWOM has a significant influence on brand attitude and purchase intention, and brand attitudes also have significant effect to the purchase intention.